Polymersomes as Novel Drug Delivery Alternative to Conventional Liposomes - Marwa malik Kamil; Mohammed J. Neamah; Yasir Qasim almajidi (College of Pharmacy / Mustansiriyah University, 2024)
The goal of medical research across the world is to improve the health of patients. Nanotechnology is an emerging field that is now heavily concentrated in the realm of medicine continuous research in the sector has resulted in the emergence of a new discipline known as "nanomedicine," which attempts to provide new treatment options while also improving the therapeutic efficacy of existing medications. polymersomes have gotten a lot of attention in recent research all around the world, and it's led to the creation of novel medical therapies. Solubilization, cancer therapy targeting, and usage as diagnostic tool are some of these techniques. Polymersomes, which are artificial amphiphilic vesicles made up of a variety of chemical polymers, are presently being investigated for delivering different probes for imaging target tissues/ organs, as well as cytotoxic medicines to tumor cells for gene therapy. Thorough analysis has been confirmed that polymersomes will surely compete in the future in the rapidly developing field of nanotechnology. Polymersomes have great stability, ease of flexibility, and capacity to encapsulate a variety of different drugs will ensure that they play a significant role in the development of sophisticated drug delivery systems.